2021
DOI: 10.1039/d1sc02547c
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced 1,2-dicarbofunctionalization of alkenes with organotrifluoroborate nucleophilesviaradical/polar crossover

Abstract: Alkene 1,2-dicarbofunctionalizations are highly sought-after transformations as they enable a rapid increase of molecular complexity in one synthetic step. Traditionally, these conjunctive couplings proceed through the intermediacy of alkylmetal species...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 103 publications
1
25
1
1
Order By: Relevance
“…Similar mechanistic scenarios have been successful in promoting a number of three-component alkene 1,2-difunctionalization reactions, including oxyalkylation, fluoroalkylation, bisalkylation, hydroesterification, , oxyamination, and diamination. , We specifically highlight the work of Chemler and Um, who demonstrated that carbamate-appended trifluoroborate salts serve as reagents for the net-oxidative synthesis of pyrrolidines from styrenes, and recent work from Ritter and co-workers demonstrated a similar concept of nucleophile-tethered reductive N -centered radical precursors for the synthesis of morpholines and homomorpholines from styrenes (Figure B) …”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Similar mechanistic scenarios have been successful in promoting a number of three-component alkene 1,2-difunctionalization reactions, including oxyalkylation, fluoroalkylation, bisalkylation, hydroesterification, , oxyamination, and diamination. , We specifically highlight the work of Chemler and Um, who demonstrated that carbamate-appended trifluoroborate salts serve as reagents for the net-oxidative synthesis of pyrrolidines from styrenes, and recent work from Ritter and co-workers demonstrated a similar concept of nucleophile-tethered reductive N -centered radical precursors for the synthesis of morpholines and homomorpholines from styrenes (Figure B) …”
mentioning
confidence: 84%
“…Our reaction design consists of a bifunctional reagent 14 carrying an NHPI ester and a tethered nucleophile, which we hypothesized would pair with an aryl alkene partner through the following sequence of elementary steps (Figure 1D). First, single-electron reduction of the NHPI ester by the excited state 34 bisalkylation, 35 hydroesterification, 36,37 oxyamination, 38 and diamination. 39,40 We specifically highlight the work of Chemler and Um, who demonstrated that carbamateappended trifluoroborate salts serve as reagents for the netoxidative synthesis of pyrrolidines from styrenes, 41 and recent work from Ritter and co-workers demonstrated a similar concept of nucleophile-tethered reductive N-centered radical precursors for the synthesis of morpholines and homomorpholines from styrenes (Figure 1B).…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Recently, dual catalysis has become a powerful approach in synthetic chemistry to overcome the limitations in traditional chemical transformations; the high energy barrier steps could be achieved under mild conditions by the combination of two different catalytic cycles. [27][28][29][30][31][32][33] Over the past few years, a variety of successful examples regarding radical umpolung chemistry enabled by dual catalysis have been developed by different research groups all over the world, mainly focusing on carbonyl functional groups (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, iridium-based photocatalyzed 1,2-dicarbofunctionalization of olefins 11 from alkyl N-(Acyloxy) phthalimide redox-active ester 12 and potassium organotrifluoroborates 13 to afford a series of corresponding products 14 (Scheme 3) was reported by Molander et al [10] The optimized conditions for this reaction were as follows: 3 mol% Ir(ppy) 3 as the catalyst in 0.1 M of MeCN at room temperature for 24 h with irradiation of blue LED. The initial reaction was performed using 4-acetoxystyrene, alkyl N-(Acyloxy)phthalimide redoxactive ester and potassium (2-phenylethynyl)trifluoroborate as model substrates.…”
Section: Introductionmentioning
confidence: 99%